STUDENTS’ E-LEARNING READINESS IN REMOTE TEACHING CONTEXT - Ariastuti, Kadek Novia; Santosa, Made Hery; Mahendrayana, Gede (International Journal of Language and Literature, 2021)
The study aims to analyze students e-learning readiness which used a mixed-method research design. There were 30 students as the subject of this study. The reliability of this research was 0.70. This study used  an online learning readiness questionnaire. For questionnaire responses, the researcher used Aydin and Tasci’s readiness measurement model to know the score of  students’ e-learning readiness. Besides that, Interview guide. The interview responses were analyzed using Interactive Model Analysis. Therefore, the students e-learning score was  Mo = 3.76. The interview result showed the availability of media and the flexibility of e-leaning as the supporting factor, while the facilities in e-learning as the limiting factor. It can be concluded that  students e-learning readiness is ready buy still need improvement on technology readiness, people readiness, innovation readiness, and self-development readiness This research was rewarding to comprehend students’ e-learning readiness as well as supporting an limiting  in  implementing e-learning in remote teaching. Several recommendations are proposed for vocational school are infrastructure provision in e-learning and socialization to use e-learning.